THE PROBLEM OF COMMUNICATION IN THE HISTORY OF PHILOSOPHICAL THOUGHT - Сластенко, Е. Ф. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
The article analizes the problems of communication in the history of global philosophical thought.